1987
DOI: 10.1111/j.1476-5381.1987.tb11289.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GABA release from slices prepared from several brain regions of rats at various times following a convulsion

Abstract: A method is described for the measurement of the K+‐evoked release of endogenous γ‐aminobutyric acid (GABA) from slices of rat cortex, hippocampus and striatum. In tissue prepared 30 min following an electroconvulsive shock, K+‐evoked GABA release (above basal release) was inhibited by 45% in cortex, 50% in hippocampus and 75% in striatum. A similar inhibition of release was observed with slices prepared from rats in which a convulsion had been induced by flurothyl. There was no change in spontaneous (basal) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
4
10
1
Order By: Relevance
“…The K+-evoked release of endogenous 5-HT and NA from slices of frontal cortex was also not statistically different for either group. These data agree with the previous work of Minchin et al (1983) The principal significance of the data obtained after a single ECS in this study, is that a normal K+-evoked release of endogenous NA and 5-HT was demonstrated at a time after a single ECS when the release of endogenous GABA was significantly inhibited (Green et al, 1987b). These results would tend to indicate the selectivity of the changes in GABAergic biochemistry following ECS, since the inhibition of endogenous GABA release does not appear to be merely a reflection of a more widespread inhibition of transmitter release in the rat brain.…”
Section: Discussionsupporting
confidence: 93%
“…The K+-evoked release of endogenous 5-HT and NA from slices of frontal cortex was also not statistically different for either group. These data agree with the previous work of Minchin et al (1983) The principal significance of the data obtained after a single ECS in this study, is that a normal K+-evoked release of endogenous NA and 5-HT was demonstrated at a time after a single ECS when the release of endogenous GABA was significantly inhibited (Green et al, 1987b). These results would tend to indicate the selectivity of the changes in GABAergic biochemistry following ECS, since the inhibition of endogenous GABA release does not appear to be merely a reflection of a more widespread inhibition of transmitter release in the rat brain.…”
Section: Discussionsupporting
confidence: 93%
“…The results were obtained by use of the technique of gas chromatography-mass spectrometry (mass fragmentography, Bertillson & Costa, 1976); however, methodological strictures including the precursor-product assumptions inherent in measuring turnover by infusion oflabelled precursors (see Bertillson & Costa, 1976) precluded the use of the method in examining turnover in brain areas such as the cortex and hippocampus. A later study by Bowdler et al (1983) confirmed and extended the observations that the GABA concentration changes in various brain regions following repeated ECS, but did not measure 'Author for correspondence; present address: Astra Neuro- The current studies have demonstrated that a single ECS or flurothyl-induced convulsion can induce marked changes in both GABA synthesis (Green et al, 1987a) and release (Green et al, 1987b) in regions of rat brain. An investigation has therefore been made of the effect of repeated seizures on GABA release in regions ofrat brain and on the rate ofGABA synthesis in various brain regions, the latter study being designed to try to confirm and extend an earlier investigation (Green et al, 1978) by use of a different methodology.…”
Section: Introductionsupporting
confidence: 64%
“…In contrast, release has returned to control values 2 h after a single ECS (Green et al, 1987b). This prolonged inhibition of striatal function following chronic ECS may reflect the very large inhibition of evoked GABA release seen with a single ECS, being of the order of a 75% inhibition of the evoked release of GABA over spontaneous efflux from the slices (compared with control values), and larger than any other area examined.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Neurotransmitters are available in several types of releasable pools (20). With initial electrical stimulation, there may be mobilization of such pools from calcium influx, but the releasable transmitter may be depleted with ongoing stimulation.…”
Section: Mechanisms Of the Postictal Statementioning
confidence: 99%